Results of the analysis of the Early Iron Age human remains unearthed at Alsónyék, Hungary: Appendix - Szeniczey, Tamás; Hajdu, Tamás (Dissertationes Archaeologicae, 2021)
The material of our examination comprise the anthropological remains of the Early Iron Age individuals unearthed at the site Alsónyék-Elkerülő 2.